2020
DOI: 10.1002/jcp.29521
|View full text |Cite
|
Sign up to set email alerts
|

CircTIMELESS regulates the proliferation and invasion of lung squamous cell carcinoma cells via the miR‐136‐5p/ROCK1 axis

Abstract: Numerous studies demonstrate that circular RNAs (circRNAs) are critical regulators of the occurrence and progression of tumors. However, research on the involvement of circRNAs in lung squamous cell carcinoma (LUSC) is limited. In our study, circTIMELESS (also named hsa_circ_0000408 in the Human circRNA Database) was upregulated in both LUSC tissues and LUSC cells, and circTIMELESS expression was positively associated with the TNM stage. Moreover, circTIMELESS silencing markedly suppressed invasion in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…TargetScan 7.2 predicted that miR-576-3p targeted ROCK1. It has been reported that ROCK1 is a downstream target of miR-136-5p and that the miR-136-5p/ROCK1 axis participates in the inflammatory response induced by cerebral ischemia/reperfusion injury, as well as in the proliferation and invasion of LSCC cells (16,17). The present study also confirmed this relationship using a dual-luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…TargetScan 7.2 predicted that miR-576-3p targeted ROCK1. It has been reported that ROCK1 is a downstream target of miR-136-5p and that the miR-136-5p/ROCK1 axis participates in the inflammatory response induced by cerebral ischemia/reperfusion injury, as well as in the proliferation and invasion of LSCC cells (16,17). The present study also confirmed this relationship using a dual-luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study reported the relationship between miR-136 and Rho-associated coiled-coil containing protein kinase (ROCK) 1 (16,17). ROCK1, one of the isoforms of the ROCK, is a downstream effector of Rho A and is activated when it selectively binds to GTP (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The circTP63/FOXM1/miR-873-3p axis is identified to facilitate LUSC progression [ 10 ]. circTIMELESS regulates LUSC cell proliferation and invasion via the miR-136-5p/ROCK1 axis [ 11 ]. In this study, the ceRNA network of circCNN2/miR-184/E2F1 was identified in LUSC cells and related assays were carried out to testify its impact on LUSC progression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-136-5p may inhibit HCC cell proliferation, migration and invasion by targeting the WNK1 pathway ( 32 ). It may also inhibit lung squamous cell carcinoma progression by deactivating ROCK1 ( 33 ). Furthermore, miR-136-5p has been reported to regulate the expression of IRX5 to suppress cell proliferation in HCC ( 34 ).…”
Section: Discussionmentioning
confidence: 99%